2009
DOI: 10.1038/sc.2009.33
|View full text |Cite
|
Sign up to set email alerts
|

Lowering body mass index cutoffs better identifies obese persons with spinal cord injury

Abstract: Study design: Cross-sectional, non-experimental design. Objectives: (1) Determine the sensitivity and specificity of the general population body mass index (BMI) cutoff for obesity (30 kg m À2 ) in a representative sample of persons with spinal cord injury (SCI); (2) develop a more sensitive BMI cutoff for obesity based on percentage of fat mass (%FM) and C-reactive protein (CRP). Setting: Ontario, Canada. Methods: A total of 77 community-dwelling adults with chronic SCI underwent anthropometric measures (%FM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
156
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(168 citation statements)
references
References 17 publications
(17 reference statements)
6
156
0
6
Order By: Relevance
“…Visceral fat area and spinal cord injury T Inayama et al able-bodied individuals often underestimate obesity in individuals with SCI. 16,17,28 Laughton et al 28 reported that BMI values 422 kg m − 2 should be considered a high risk for obesity and obesity-related chronic diseases for individuals with chronic SCI. Buchholz and Bugaresti 13 noted that BMI has low sensitivity as an indicator of obesity in individuals with SCI and recommended that SCI-specific BMI classifications be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Visceral fat area and spinal cord injury T Inayama et al able-bodied individuals often underestimate obesity in individuals with SCI. 16,17,28 Laughton et al 28 reported that BMI values 422 kg m − 2 should be considered a high risk for obesity and obesity-related chronic diseases for individuals with chronic SCI. Buchholz and Bugaresti 13 noted that BMI has low sensitivity as an indicator of obesity in individuals with SCI and recommended that SCI-specific BMI classifications be determined.…”
Section: Discussionmentioning
confidence: 99%
“…19 In fact, recent recommendations are to consider people with chronic SCI and BMI values >22 kg/m 2 as being at high risk for obesity and obesity-related chronic diseases. 22 Growing evidence supports the contention that excess adiposity, especially abdominal adiposity, is the driver of the metabolic syndrome due to its secretion of proinflammatory cytokines, hypertensive agents and nonesterified free fatty acids that contribute to hypertension, dyslipidemia, insulin resistance and atherosclerosis. 5,6 Appropriate characterization of obesity and body composition changes in SCI is essential for ongoing evaluation of the metabolic syndrome.…”
mentioning
confidence: 99%
“…Table 2 presents anthropometric and biochemical data of the patients [2124]. According to Laughton et al [21], since a BMI score of >22 is overweight and >25 is obese, 62.96 (n = 102) and 32.71 (n = 53) percent of the patients in this study were classified as overweight and obese, respectively. Table 3 compares mean ± standard deviation for cardiometabolic risk factors in tetraplegic and paraplegic and complete and incomplete groups.…”
Section: Resultsmentioning
confidence: 99%